PELATIHAN AKUNTANSI UNTUK SMA: : Persamaan Dasar, Penggolongan Akun,dan Penyusunan Laporan Keuangan - Agustin Ekadjaja; Rachel Christabella; Jessica Octaviani; Clara Felixa Tridian (LPPM ITB AAS Indonesia Surakarta, 2026)
This accounting training program for high school students is designed as a means of strengthening financial literacy through the introduction of applicable basic accounting concepts. The focus of the activity is directed at understanding the basic equations of accounting, account classification, and the skills of compiling simple financial reports for trading companies. The training method integrates material presentation, interactive discussions, and financial report preparation practices. The implementation of the activity began with the identification of school needs, then continued with the preparation of modules that emphasized the relationship between transaction recording, account classification, and the presentation of income and balance sheet reports. The expected results include improving students' analytical skills, skills in managing accounting data, and the formation of a thorough and logical attitude in understanding the flow of financial information. As an academic output, this activity produces training modules that have the potential to be developed as Intellectual Property Rights, scientific publications, and evaluation reports to related institutions. This training model is expected to be replicated in other schools as a real contribution of universities in expanding accounting literacy and supporting the readiness of the younger generation to face the business world in a sustainable manner. This activity is expected not only to improve student competence, but also to have a positive impact on the development of accounting education at the secondary school level. This activity also develops soft skills such as teamwork, communication, and problem-solving. In addition, this activity can be a bridge for students who want to continue their studies in accounting or finance. The implementation of this program can also increase students' awareness of the importance of financial literacy in daily life so as to provide long-term benefits for students and society. Keywords: Accounting; Basic Accounting Equations; Account classification; Financial Statements; Financial Literacy. Abstrak Program pelatihan akuntansi bagi siswa SMA ini dirancang sebagai sarana penguatan literasi finansial melalui pengenalan konsep dasar akuntansi yang aplikatif. Fokus kegiatan diarahkan pada pemahaman persamaan dasar akuntansi, penggolongan akun, serta keterampilan menyusun laporan keuangan sederhana untuk perusahaan dagang. Metode pelatihan mengintegrasikan pemaparan materi, diskusi interaktif, dan praktik penyusunan laporan keuangan. Pelaksanaan kegiatan diawali dengan identifikasi kebutuhan sekolah, kemudian dilanjutkan dengan penyusunan modul yang menekankan keterkaitan antara pencatatan transaksi, klasifikasi akun, hingga penyajian laporan laba rugi dan neraca. Hasil yang diharapkan mencakup peningkatan kemampuan analisis siswa, keterampilan dalam mengelola data akuntansi, serta terbentuknya sikap teliti dan logis dalam memahami aliran informasi keuangan.Sebagai luaran akademik, kegiatan ini menghasilkan modul pelatihan yang berpotensi dikembangkan sebagai Hak Kekayaan Intelektual, publikasi ilmiah, serta laporan evaluasi kepada lembaga terkait. Model pelatihan ini diharapkan dapat direplikasi di sekolah lain sebagai kontribusi nyata perguruan tinggi dalam memperluas literasi akuntansi dan mendukung kesiapan generasi muda menghadapi dunia usaha secara berkelanjutan. Kegiatan ini diharapkan tidak hanya meningkatkan kompetensi siswa, tetapi juga memberikan dampak positif bagi pengembangan pendidikan akuntansi di tingkat sekolah menengah. Kegiatan ini juga mengembangkan keterampilan soft skills seperti kerja sama tim, komunikasi, dan pemecahan masalah. Selain itu, kegiatan ini dapat menjadi jembatan bagi siswa yang ingin melanjutkan studi di bidang akuntansi atau keuangan. Implementasi program ini juga dapat meningkatkan kesadaran siswa tentang pentingnya literasi finansial dalam kehidupan sehari-hari sehingga memberikan manfaat jangka panjang bagi siswa dan masyarakat. Kata Kunci : Akuntansi; Persamaan Dasar Akuntansi; Penggolongan Akun; Laporan Keuangan; Literasi Finansial.